2017
DOI: 10.1007/s00442-017-4040-z
|View full text |Cite
|
Sign up to set email alerts
|

Testing the hypothesis of hierarchical predictability in ecological restoration and succession

Abstract: To advance predictive ecology, the hypothesis of hierarchical predictability proposes that community measures for which species are interchangeable (e.g., structure and species richness) are more predictable than measures for which species identity matters (e.g., community composition). Predictability is hypothesized to decrease for response measures in order of the following categories: structure, species richness, function, and species composition. We tested this hypothesis using a 14-year, oak savanna-prair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Although species composition may provide indications of a much wider range of ecosystem properties than aggregated, more generic properties of vegetation such as total cover and species richness, the latter are much more often used to assess restoration success (Ruiz‐Jaén & Aide, ; Waldén & Lindborg, ). Which metrics to use is still vigorously debated (Abella, Schetter, & Walters, ; Brudvig et al, ; Durigan & Suganuma, ; Reid, ). In general, we expect species composition to recover more slowly than total cover and species richness.…”
Section: Introductionmentioning
confidence: 99%
“…Although species composition may provide indications of a much wider range of ecosystem properties than aggregated, more generic properties of vegetation such as total cover and species richness, the latter are much more often used to assess restoration success (Ruiz‐Jaén & Aide, ; Waldén & Lindborg, ). Which metrics to use is still vigorously debated (Abella, Schetter, & Walters, ; Brudvig et al, ; Durigan & Suganuma, ; Reid, ). In general, we expect species composition to recover more slowly than total cover and species richness.…”
Section: Introductionmentioning
confidence: 99%
“…In tropical trees, plot‐scale variation in species richness is tightly linked to variation in tree abundance (Condit et al., 1996); therefore, it is unsurprising that recovery of plant richness and total abundance present the same amount of variation. It is important to note that other researchers comparing the predictability of distinct ecological metrics in the context of ecosystem restoration focused exclusively on plants (Abella et al., 2018; Laughlin et al., 2017; Rosenfield & Müller, 2017), highlighting the need to expand the taxonomic scope of predictive restoration ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Time‐to‐recovery predictions by ORBA for our study sites showed similar degrees of uncertainty, expressed as 95% CI of model estimates, for functional trait composition (this study) and species composition (Rydgren et al 2020). Laughlin et al (2017) found functional trait‐based metrics to be less variable and more predictable than species composition‐based metrics for a variety of restoration treatments, while Abella et al (2018) questioned the existence of a general hierarchy of predictability. Thus, the two types of metrics should be considered as complementary for predictions of time to recovery as well as for recovery assessments.…”
Section: Discussionmentioning
confidence: 99%